Analysis of Ecotourism Development Potential of Laut Tinggal Lake, West Sumatera - Siburian, Siti L; Widyawiratma, Anggara; Ghimar, Migo F; Hapsari, Shafia R; Prabawa, Khasya F; Putro, Haryanto R; Kusrini, Mirza D; Putra, Erianto I (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
Danau Laut Tinggal of West Sumatra has a significant potential for ecotourism if managed properly. Therefore, an ecotourism management plan is needed, which includes assessing tourism suitability, biodiversity along hiking trails and around the lake, as well as community readiness for ecotourism development in the Danau Laut Tinggal area. The methods used include assessing the feasibility of tourist attractions, analyzing the suitability of lake water tourism, inventorying fauna and biodiversity, and analyzing community readiness. The research results show that Danau Laut Tinggal is suitable to be developed for ecotourism, supported by the readiness of the local community to participate in ecotourism management and the discovery of various biodiversity, including 60 species of flora, 13 species of mammals, and 29 species of avifauna, some of which are endangered, such as the Rhinoceros Hornbill, Crested Serpent Eagle, and Agile Gibbon. Keywords: biodiversity, community readiness, ecotourism, laut tinggal lake, management